Kosakata Siswa Sekolah Dasar Kelas Rendah (Kajian Jenis Kata, Bentuk Kata, Jenis Makna, dan Medan Makna) - Mulyati, Yeti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
This study aimed to describe the vocabulary of low grade primary school students based on the type and form of the word, and also the type and semantics domain. Source of research data is in the form of students written language derived from the essays of graders 2 and 3 from 6 elementary schools in Bandung. The data were analyzed qualitatively. The results showed: 1) the type of words made up of nouns (37%), verbs (35%), adverbial (10%), function words (9%), pronouns (5%), numeralia (3%), and adjectives (1%); 2) forms of words consist of basic words (62%), derivational words (28%), particle (0.8%), reduplicative words (0.2%), compound words, (0.01); 3) classification of the meaning consists of referential meaning (87%) and nonreferential meaning (13%); and 4) semantics domain include: motion-employment (29%), function words (13%), personal pronouns /reference (10%), nature (7%), tempe-rament/properties/color (5%), animals ( 4.7%), the life of the community (4.6%), games (2.7%), home/parts (2.4%), numeral words (2.3%), food/beverages (1.8%), body parts (1.4%), disease-treatment 91.3%).